Por um cinema de poesia mestiço: o filme Caramujo-flor de Joel Pizzini e a obra poética de Manoel de Barros - Torchi, Gicelma da Fonseca Chacarosqui (2008)
The aim of this research is the study of the intersemiotics translations made by the filmic work of Joel Pizzini Caramujo-flor(Clam-flower) re(reading) the verbal and visual signs that are interlaced in the construction of the poetic text of Manoel de Barros´s work Gramática Expositiva do Chão-Poesia quase toda. We started from the problem that the semiotics relationships between the poetic of Manoel de Barros and the film Caramujo-flor (Clam-flower) constitute what we can call Movies of Poetry. Therefore, our aim is to analyze the film and the poems that make it, in a correlating way, to prove the raised problem. This analysis was developed around three significant axes: the metaphor of the mosaic that translates the intersemiotics relationships; the fictional imaginary and its presence in culture, going through the Baroque and the eroticism of the poetic word and its recreation in the filmic object; finally, how the proliferous relationship of the intertextual, metalinguistic and hybridization elements influence the semiotic-cultural mediations accomplished by the medias, especially the movies. We articulated, therefore, as first hypothesis, that Clam-flower, when proposing a new look on the appealing narrative structures of the independent movies, enrolls in what Buñuel and Pasolini call Movies of Poetry . As a methodological approach, we will use the necessary bibliographical research instead of the analysis of the procedures on the construction of the studied works. Based on the authors that study movies and in the translating theories between semiotics and movies, joined to Joel Pizzini's and Manoel de Barros bibliographies. The based theory is the semiotics of lotmaniana root, in which the dialogue among the cultural compounds permeates the frontier zones of the arts, promoting generating spaces of sense that move dynamically. Concerning movies, we will use the theories of Eisenstein, Pasolini and Buñuel. In order to elucidate the questions concerning the Baroque, we will read Sarduy and Haroldo de Campos. We also point out authors as Paul Zumthor, who works with the performance specification of the oral language. We also go through the translation theorists (from Benjamin to the concretes) along with those of the miscegenation (Laplantine, Gruzinski, Amálio Pinheiro, etc)